Optimasi komposisi belimbing wuluh (Averrhoa bilimbi L.) dan gula terhadap karakteristik fisikokimia selai - Juanda Juanda; Raida Agustina; Sri Hartuti (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
Bilimbi is a plant with many benefits. One of the product diversifications made from the bilimbi is a jam. Making bilimbi jam by mixing fruit fiber and sugar and then cooking it for 5 minutes. Nowadays, fruit jams with various flavor variants are liked by people from various circles, so the bilimbi jam has an excellent opportunity to be developed. This study aimed to determine the effect of the number of ingredients and the amount of sugar on the physicochemical properties of bilimbi jam, and,: to determine the optimal composition of raw materials using response surface methodology (RSM). Optimization using response surface methodology is able to get the best treatment combination effectively. The analysis of the physicochemical properties of bilimbi jam included pH, total dissolved solids, water content, vitamin C, greasing power, chroma color, and hue. The raw material composition for making bilimbi jam is the amount of bilimbi (X₁) of 659 g and the amount of sugar (X₂) of 137 g. The predicted response value for pH (Y₁) is 3.2, TPT (Y₂) is 16.01, vitamin C (Y₃) is 20 mg/100 g, moisture content (Y₄) is 30 %, oil power (Y₅) is 9.51 cm, color chroma (Y₆) of 48.86, and hue (Y7) of 78.17.